Jungle Math: An Educational Mobile Games for Preschoolers Learning Mathematics - Dawson, Jade Geraldine Manomony; Hibadullah, Cik Fazilah; Munya Saleh Ba Matraf; Harun, Nor Hazlyna; Hashim, Nor Laily; Dahari, Rohaya (Emerging Advances in Integrated Technology, 2023)
This project is about developing an educational game for kindergarten children. Educational games for kids are designed to teach important concepts such as numbers, letters, colours, shapes, and more in a fun and engaging way. They can also help develop important skills such as problem-solving, critical thinking, and creativity. Mathematics is a challenging subject for most children at an early age, especially preschoolers. This is due to the lack of understanding, interest, and successful ways to help them learn. Typically, mathematical games are presented with an emphasis on entertainment or education. Games can be an effective way to teach children mathematics. They can also help foster a positive attitude towards the subject, which can lead to better learning outcomes. Thus, creating an educational mobile game would be an excellent solution to this problem. This project aims to create a mobile game that can be installed on mobile phones or tablets to teach children mathematics. The RAD (Rapid Application Development) model will be used as the project methodology to conduct this project. First, the functional requirements were determined. Then, the prototype was developed and named Jungle Math. A field usability test was conducted with the targeted users to evaluate the application's ease of use. The findings suggest that the application is ready to be used in a learning and fun environment for kindergarten children upon the success of the trial run, as the targeted users found the application easy to use and enjoyed playing and learning with the application.